What drives passengers towards sustainable aviation? A segmentation study of travel behaviour and environmental concern in Spain - Patino-Artaza, Helena; Suau-Sanchez, Pere (Elsevier, 2025)
Air travel significantly contributes to greenhouse gas emissions, posing challenges for climate action. This study examines the attitudes and behaviours of Spanish air passengers, focusing on the relationship between environmental concerns and travel choices. Based on a survey of 1,206 participants, we employed exploratory factor analysis to identify three attitudinal clusters: “Status quo flyers,” “Environmentally conscious low-flyers,” and “Pragmatic moderates”. These segments display significant differences in travel frequency, environmental concern, perception of aviation’s impact, and willingness to adopt sustainable alternatives. While environmentally conscious travellers express willingness to reduce air travel, frequent flyers often resist behavioural changes, highlighting a persistent attitude-behaviour gap. The results emphasise the importance of targeted strategies to address the attitude-behaviour gap and promote sustainability in aviation. This research provides actionable insights for policymakers and industry stakeholders to foster sustainable travel behaviours in one of Europe’s largest aviation markets.
Keywords: 3508 Tourism; 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; 13 Climate Action; 12 Responsible Consumption and Production; Air travel; Aviation; Sustainability; Climate change; Survey; Passenger segmentation; Spain